Bulgaria : 2019 Article IV Consultation-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Bulgaria. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that economic performance remains robust but risks to the outlook are tilted to the downside amid slowing external demand. Sound macroeconomic policies notwithstanding, Bulgaria faces a sizable income gap vis-a-vis the EU average and unfavorable demographic prospects. The main policy challenge is to raise growth potential, which calls for broad-based structural reforms to improve public goods provision and institutions. The Article IV discussions focused on medium-term reforms to improve public goods provision and raise potential growth and on near-term policies to enhance financial sector stability. Fiscal policy is broadly appropriate, but the efficiency of spending and revenue administration could be further improved. Stronger public investment management would improve investment efficiency and transparency. Better performance of state-owned enterprises would help raise growth potential and mitigate fiscal risks. Bank profits have risen and non-performing loans (NPLs) have continued to decline, although they are still high among EU countries. The central bank should ensure that banks with high NPLs have adequate capital buffers.